Traditional Healthcare delivery systems in the 21st century Nigeria: moving beyond misconceptions (2008)
One of the most notable features of medicine in the later part of the preceding century were vigorous criticisms against traditional systems of healthcare delivery, almost to a point of suffocation. Although most of the issues raised to affirm the seemingly inadequate status of this system are compelling, its absolute undesirability has been difficult to establish. Part of the misconception derives from lumping Nigeria into one integrated and indivisible indigenous unit, notwithstanding differences in values, beliefs and practices among communities. Against this backdrop, this study invites a reassessment and possible integration of Nigerian traditional medicine with the introduced systems of healthcare delivery. This will ensure not only a holistic approach to dealing with complex health issues among Nigerians, but also the continued relevance of indigenous medicine. Critical issues examined include forms and factors affecting traditional medicine, and conflicts between indigenous and introduced systems of healthcare delivery. Consequently, a framework for explaining traditional medicine in the context of Nigeria was designed through a triangulation of Rational Choice theory, Ethnomethodology and the Health Belief Model.